Wizard's first rule - Goodkind, Terry (Goodkind, Terry. Sword of truth, 2022)
Richard Cypher, a woodsman, saves Kahlan, a beautiful woman who is fleeing the evil mage Rahl's assassins as she tries to find Zedd, the last of the great wizards. Only Zedd can anoint a Seeker of Truth, who must wield the terrible power of the legendary Sword of Truth. Zedd calls upon Richard to become the seeker and battle the evil mage.